The Interrelationship of Leisure and Play - Stebbins, Robert A. author. aut Link
VII, 183 p.
Keywords: Augmentative play is a special activity that substantially aids the pursuit of a larger, encompassing leisure activity. This approach to the study of play is unique. It recognizes the hundreds of activities in which play and leisure come together.